Transfer of Salmonella Enteritidis to four types of surfaces after cleaning procedures and cross-contamination to tomatoes - Soares, Vanessa Mendonca [UNESP]; Pereira, Juliano Goncalves [UNESP]; Viana, Cibeli [UNESP]; Izidoro, Thiago Braga [UNESP]; Bersot, Luciano dos Santos; Pinto, José Paes de Almeida Nogueira [UNESP] (Academic Press Ltd Elsevier B.V. Ltd, 2012)
The objectives of the present study were to evaluate the spread of Salmonella Enteritidis to different cutting boards (wood, triclosan-treated plastic, glass, and stainless steel) from contaminated poultry skin (5 log CFU/g) and then to tomatoes and to analyze the effect of different protocols used to clean these surfaces to control contamination. The following procedures were simulated: (1) no cleaning after handling contaminated poultry skin; (2) rinsing in running water; (3) cleaning with dish soap and mechanical scrubbing; and (4) cleaning with dish soap and mechanical scrubbing, followed by disinfection with hypochlorite. The pathogen was recovered from all surfaces following procedure 1, with counts ranging from 1.90 to 2.80 log, as well as from the tomatoes handled on it. Reduced numbers of S. Enteritidis were recovered using the other procedures, both from the surfaces and from the tomatoes. Counts were undetectable after procedure 4. From all surfaces evaluated, wood was the most difficult to clean, and stainless steel was the easiest. The use of hypochlorite as a disinfecting agent helped to reduce cross-contamination. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Cleaning; Cross-contamination; Cutting boards; Salmonella Enteritidis